2019
DOI: 10.1111/jsr.12964
|View full text |Cite
|
Sign up to set email alerts
|

The effect of night‐time exercise on sleep architecture among well‐trained male endurance runners

Abstract: Ensuring balance between training load and recovery is essential for optimal athletic performance and success in competition (Mujika, Halson, Burke, Balague, & Farrow, 2018; Nedelec et al., 2013). Both athletes and the scientific community agree that sleep is one of the most important components for recovery in elite sport (Halson, 2008; Venter, 2014). Moreover, a growing body of scientific evidence confirms the negative impacts that sleep loss can have on physical performance (Mougin et al., 1989) and cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 39 publications
4
37
2
Order By: Relevance
“…Finally, an important caveat remains that the effects we observed in the TS condition (experiment 2) and, especially, in the running wheel condition (experiment 1) as compared to exploratory wakefulness may be, at least to some extent, be accounted for by the different amount or intensity of physical activity. Previous human studies have shown that exercise can promote sleep [ 54 56 ], and acute exercise before bedtime can increase sleep amount [ 57 , 58 ], but could also interfere with deep NREM sleep in the first hours of sleep [ 59 ]. We did not observe any disruption in NREM sleep after our manipulations, but additional studies are necessary to further investigate the role of physical activity associated with different behaviours on sleep and sleep homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an important caveat remains that the effects we observed in the TS condition (experiment 2) and, especially, in the running wheel condition (experiment 1) as compared to exploratory wakefulness may be, at least to some extent, be accounted for by the different amount or intensity of physical activity. Previous human studies have shown that exercise can promote sleep [ 54 56 ], and acute exercise before bedtime can increase sleep amount [ 57 , 58 ], but could also interfere with deep NREM sleep in the first hours of sleep [ 59 ]. We did not observe any disruption in NREM sleep after our manipulations, but additional studies are necessary to further investigate the role of physical activity associated with different behaviours on sleep and sleep homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…increased muscle damage) 2 , though such mechanisms have not gained appraisal. 35 It is perhaps more plausible that the core players may have experienced a change in their mood (i.e. elation or tension) as a result of the match outcome that meant they adopted a later bedtime than usual.…”
Section: Sleep Comparison Between Night After Match and Training Nightsmentioning
confidence: 99%
“…Based on a previous study (Aloulou et al, 2019), we estimated that a sample size of 12 subjects would allow us to detect differences in MVIC after a simulated trail with power (1β) set at 0.80, a large effect size (>0.8) and an alpha of 0.05. Post-hoc power analysis revealed that this study was adequately powered, with actual power (1β) > 0.90 (G * Power program version 3.1.9.7).…”
Section: Resultsmentioning
confidence: 99%
“…For each experimental condition, participants completed a simulated trail adapted from Aloulou et al (2019). The exercise lasted 48 min with five 9-min blocks and was shown to elicit a significant level of fatigue and muscle damage until 48 h after exercise (Aloulou et al, 2019). Heart rate (HR) was measured throughout the exercise.…”
Section: Simulated Trailmentioning
confidence: 99%